Comparison of the Pain Sensitivity Questionnaire and the Pain Catastrophizing Scale in Predicting Postoperative Pain and Pain Chronicization After Spine Surgery. Issue 9 (November 2018) - Tuna, Turgay; Boz, Sibel; Van Obbergh, Luc; Lubansu, Alphonse; Engelman, Edgard
Abstract : Study Design: This was a prospective study evaluating the Pain Sensitivity Questionnaire (PSQ) in 110 patients undergoing spine surgery. Objective: The purpose of this study was to compare the ability of the PSQ-total and PSQ-minor scores with the Pain Catastrophizing Scale (PCS) in predicting the immediate postoperative pain of patients after spinal surgery and their risk of developing a chronically painful state. Summary of Background Data: Studies evaluating the PSQ as a preoperative determinant for the development of chronic pain are lacking. Therefore, we undertook the following study. Materials and Methods: Patients undergoing lumbar or cervical spine surgery were prospectively included in the study. The PSQ-total and PSQ-minor, the PCS and its subscores, the Oswestry Disability Index (ODI) and the Neck Disability Index were used preoperatively. Preoperative and postoperative Visual Analog Scale scores for pain at rest and movement and analgesics were recorded. At 12 months postoperatively, the Neck Disability Index and the ODI were once more assessed to evaluate pain chronicization. Results: A total of 110 patients scheduled to undergo surgery at our spine center participated in the study. Our results highlighted that Visual Analog Scale scores were increased for high catastrophizers at rest on the first postoperative day when compared with low catastrophizers. Preoperative use of opioids and a high score on the rumination subscale of the PCS were linked to greater postoperative morphine consumption. At 12 months, the PCS, the PSQ-total, and PSQ-minor showed correlations with the development of a chronically painful state for ODI scores >21, indicating a marked persistent disability. Conclusions: Both PSQ and PCS showed an ability to predict a chronically painful state as defined by the persistence of disability after lumbar surgery.